2021
DOI: 10.1002/pon.5692
|View full text |Cite
|
Sign up to set email alerts
|

Assessing neuropsychological phenotypes of pediatric brain tumor survivors

Abstract: Introduction Pediatric brain tumor survivors (PBTS) are at risk for both neurocognitive impairments and psychological difficulties, yet these two domains have historically been discretely examined, with assessment of psychosocial outcomes rarely included in studies of cognitive outcomes. Taking a person‐centered approach, the current study aimed to more comprehensively evaluate PBTS late effect profiles, including both neurocognitive and psychological sequelae, and predictors of these profiles. Method PBTS (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Notably, several studies have reported that internalizing problems are more frequent in PBTSs than externalizing behaviors [10,87,99]. Accordingly, we observed that the per-centage of patients with clinically relevant internalizing symptoms was higher than the percentage of those displaying externalizing problems (see Results; Figure 1a).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Notably, several studies have reported that internalizing problems are more frequent in PBTSs than externalizing behaviors [10,87,99]. Accordingly, we observed that the per-centage of patients with clinically relevant internalizing symptoms was higher than the percentage of those displaying externalizing problems (see Results; Figure 1a).…”
Section: Discussionmentioning
confidence: 51%
“…Among the main complications, PBTSs experience internalizing problems, related to withdrawal, anxiety, depression [9,10], somatization [4], difficulties in social functioning and acceptance, especially by peers [11][12][13]. Moreover, pediatric cancer survivors may also develop in a low percentage of cases post-traumatic stress disorder symptoms (4.7%-21%) [14,15] and suicidal ideation (6-8%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The ATRT‐Neuropsychology Tool has been implemented in the randomized trial SIOPE ATRT01 (EudraCT 2018‐003335‐29). Analyses should also comprise molecular subgrouping, 53 biomarkers, 54 socioeconomic status, 55 family functioning, 32 neurocognitive profiles, 56 and participation in everyday‐life after treatment 57 …”
Section: Discussionmentioning
confidence: 99%
“…There was a significant level of heterogen ity across the different studies (I 2 = 54%, p < 0.01) and no significant publication bias w identified t (15) = 0.36, p = 0.72, Figure S5a. 2021) [83] reported more than o independent cohort in their study [24,30,36,37,39,40,42,43,[45][46][47]49,[55][56][57][58]60,61,[63][64][65][66][70][71][72][73][74][75]77,83]. (a) Abso-lute risk-attention problems; (b) Absolute risk-emotional; (c) Absolute risk psychosocial problems…”
Section: Absolute Risk-attention Problemsmentioning
confidence: 98%